Dialect density, language abilities and emergent literacy skills of prekindergarten children who speak African American English. (23rd September 2022) - Baldwin, Erika; Heilmann, John; Finneran, Denise; Cho, Chi C.; Moyle, Maura
Abstract : Background: Numerous studies have observed a significant and unique relationship between children's use of nonmainstream dialect and reading outcomes. We aimed to examine the relationship between nonmainstream dialect and reading at its roots by completing a preliminary evaluation of the relationship between African American English (AAE) dialect and multiple dimensions of emergent literacy skills in young African American children enrolled in Head Start. Methods: Seventy‐eight African American preschoolers completed the Phonological Awareness Literacy Screening‐PreK (PALS‐PreK) and a narrative retell of the wordless picture book, Frog, Where Are You? The narratives were used to generate three measures of narrative productivity and the dialect density measure (DDM). Results: Structural equation modelling found that the PALS‐PreK measures significantly loaded onto a single print‐related emergent literacy latent variable and that the three narrative measures significantly loaded onto a single language‐based emergent literacy latent variable. There was a significant relationship between print‐related emergent literacy skills and DDM, but the overall model had a poor fit, showing that the relationship between emergent literacy and DDM was weak. Conclusions: We conclude the manuscript by discussing implications of this research and suggestions for further study. Highlights: What is already known about this topic African American English dialect use has a unique and complex relationship with reading outcomes. African American English dialect use can have a significant relationship with children's emergent literacy skills. What this paper adds Narrative and print‐related skills are distinct dimensions in young children who speak African American English. African American English dialect use has a modest relationship with emergent literacy measures in young children with fledgling emergent literacy skills. Implications for theory, policy or practice Whereas African American English has a significant, unique and complex relationship with formal reading skills, our research indicates that the relationship between African American English use and emergent literacy skills is modest. Because African American English dialect can be a key part of cultural identity, it is important that early childhood educators are respectful of their students' dialect use.